INTEGRATING CRITICAL LITERACY AND LOCAL WISDOM: A STUDY OF BATAK ANGKOLA CULTURAL DISCOURSE IN INDONESIAN EFL HIGHER EDUCATION - Ramadhani, Yulia Rizki; Tambunan, Elissa Evawani; Harputra, Yuswin; Sibuea, Bismar; Harahap, Nursaima (Jurnal Ilmiah Spectral, 2025)
Critical literacy in English language education plays a role in developing reading and writing skills, while also integrating learning with everyday life. However, some researchers have found a lack of literacy activities in Indonesia, particularly at the higher education level. This study explores the application of a critical literacy approach in English language learning through the discourse analysis of Batak Angkola local wisdom. This classroom action research involves 8 EFL students. The study examines the development patterns of students' critical literacy, their change in perspective towards the values of local wisdom, and identifies the challenges and benefits of applying the critical literacy approach. The results show that the critical literacy approach improved students' analytical skills from 65 to 85, their understanding of philosophical values from 30% to 85%, and their awareness of cultural preservation from 40% to 95%. There were also improvements in English language skills and other competencies, such as leadership, presentation, collaboration, self-contribution, respect, critical thinking, and the broadening of perspectives through discussions. This study contributes to the development of English language teaching methods integrated with the preservation of local wisdom.